Nutrition challenges ahead - Chen, J.; Fewtrell, M.; Kennedy, G.; Naska, A.; Riediger, K.; Roos, N.; Sanders, T.; Tuohy, K.M.; Valtuena-Martinez, S. (Wiley, 2016)
The breakout session ‘Nutrition challenges ahead’ was held at the EFSA 2nd Scientific Conference ‘Shaping the Future of Food Safety, Together’ (Milan, Italy, 14–16 October 2015) to address the main problems in the area of nutrition to be faced in the 21st Century, both at a global and individual level. The nutrition challenges ahead are diverse and depend on agricultural, socioeconomic and individual factors. At a global level, food security, food sustainability and decreasing the impact of food production on climate change are of paramount importance. Decreasing the prevalence of obesity and related disorders, which may coexist with selected micronutrient deficiencies, is a major challenge for wealthy countries; for developing countries and rural food systems, fighting protein–energy malnutrition and micronutrient deficiencies is a priority. Diets based on a wide variety of nutrient-rich local plant foods (e.g. fruits, vegetables, whole grain cereals, vegetable oils, nuts) that contain moderate amounts of animal protein (preferably in the form of fish) and are low in saturated and trans-fatty acids, added sugars and sodium, are healthy, nutritious, sustainable and climate friendly. Creating an environment where such diets are also economically advantageous and convenient may be a part of a global solution to these nutritional challenges. Individuals, however, are unique regarding their genetic background, gut microbiota and health status. In addition, nutrition may already play a role in the development (and prevention) of disease very early in life. Thus, additional health benefits could be achieved by tailoring nutritional strategies to particular population subgroups or even individuals on the basis of current and future knowledge about the relationship between nutrients, genes, the microbiome and health. New technologies and food innovation may help in finding novel foods fit for purpose.